2009
DOI: 10.1143/jjap.48.111408
|View full text |Cite
|
Sign up to set email alerts
|

Mn-Doped BaTiO3Thin Film Sintered Using Nanocrystals and Its Dielectric Properties

Abstract: BaTiO 3 thin films homogeneously doped with Mn were prepared by a novel powder-sintering thin-film process. Mn-doped BaTiO 3 nanocrystals 5 -7 nm in diameter were synthesized by a sol-gel method and sintered to form a highly densified microstructure containing columnar grains epitaxially grown on a (111)-oriented Pt/TiO 2 /Al 2 O 3 substrate at a low temperature of 800 C. On the basis of the results of various structural analyses, Mn was suggested to act as an acceptor in the perovskite structure of BaTiO 3 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The Mn ions in BaTiO 3 have a fluctuating valence state between +2 and +4, which can compensate for the oxygen vacancies to keep the sample electrically neutral. [28] Mn dopant ions act as acceptors in the BaTiO 3 thin films and thus form positively charged trapping centres in the band gap. The trapping process can be described as follows:…”
Section: Resultsmentioning
confidence: 99%
“…The Mn ions in BaTiO 3 have a fluctuating valence state between +2 and +4, which can compensate for the oxygen vacancies to keep the sample electrically neutral. [28] Mn dopant ions act as acceptors in the BaTiO 3 thin films and thus form positively charged trapping centres in the band gap. The trapping process can be described as follows:…”
Section: Resultsmentioning
confidence: 99%
“…At low frequency, those trapping centers cause the increase of tanδ. 24 The ε r of the BTMO-100 and BTO-100 thin films is rather constant over the entire investigated frequency range. The ε r of the BTMO-100 thin films is smaller than that of the BTO-100 thin films, indicating that an excessively high concentration of Mn-doping decreases the ε r of BTMO thin films.…”
Section: (B)]mentioning
confidence: 93%
“…The Mn ions in BaTiO 3 have a fluctuating valence state between +2 and +4, which can compensate the oxygen vacancies to keep the sample electrical neutral. 24 Mn ions act as acceptors in the Mn-doped BaTiO 3 thin films and thus form positively charged trapping centers in the band gap. The trapping process can be described as follows: 25 Mn Ti × + e ' ↔ Mn Ti '…”
Section: (B)]mentioning
confidence: 99%
See 1 more Smart Citation
“…These requirements were met through optimization of processing parameters and incorporation of appropriate dopants at optimum concentrations. It has been well established that Mn doping is effective in achieving of high insulation resistance in BaTiO 3 ‐based dielectrics, 16,17 In Mn‐doped BaTiO 3 , oxygen vacancies ( V O •• ) and ionized acceptors (Mn′ Ti and/or Mn″ Ti ) are the dominant defects, which prevent the reduction of BaTiO 3 (in reduced BaTiO 3 oxygen vacancies and electrons are the dominant defects). In addition, it was reported that dielectric loss (at 3 GHz) of TiO 2 ceramics was greatly reduced by introducing divalent or trivalent dopants with ionic radius in the range of 0.50–0.95 Å (ionic radius of Mn 2+ : 0.80 Å), as the reduction of Ti 4+ was prevented 18 .…”
Section: Introductionmentioning
confidence: 99%